KEDUDUKAN DAN FUNGSI PESINDEN WAYANG MALANGAN DI KELUARGA, KOMUNITAS SENI PERTUNJUKAN DAN MASYARAKATNYA Kajian Budaya, Analisis Gender - Henricus Supriyanto (Litbang STFT Widya Sasana Malang, 2006)
This study tries to expose traditional singer (pesinden) or waranggana life in Kota Malang and Kabupaten Malang. Gender analysis aimed is an analysis carried out to recognize conditional background and problems causing different roles between women and men. Theory used is Giele theory (1977) modified by Hagul (1987: 2-3). This theory focuses on some options taken in life (life option) of traditional singer (pesinden) in Malang. Six measurements used include political activity and behavior, free movement in job field, family establishment and pesinden rights, educational level she reaches, health and sexual attitude in her family and cultural expression in wayang entertainment art community. Those six measurements are used to recognize the status and role of pesinden in family, entertainment art community, and public. Pesinden position in her family is her right in selecting her husband, living right in sexual aspect and her right to propose divorce if there is unharmony in her family, the high status of pesinden in entertainment art community with special reward as high as main ‘level’ niyaga (traditional music player) and status of pesinden in her public with good ‘image’ in her audiences eyes. Pesinden function in her family as mother, as main supporting artist in entertaiment art community and as public organization pioneer in her community.